PHYTOTONIC EFFECTS OF NEONICOTINOID INSECTICIDES IN COWPEA AND GREEN GRAM - ANTU, MITHU; KORAT, D. M (The Bioscan, 2016)
Field experiments were conducted during summer and kharif, 2013 to study the phytotonic effects of neonicotinoid insecticides (imidacloprid, thiamethoxam and acetamiprid) as seed treatment alone and in combination with one (30 days after germination, DAG) or two foliar sprays (30 and 45 DAG) in cowpea and green gram. All the treatments of thiamethoxam (68.25 to 68.72 cm and 63.86 to 64.92 cm in cowpea (CP) and green gram (GG) respectively) significantly increased the plant height followed by imidacloprid (63.22 to 64.22 and 59.08 to 60.09 cm in CP and GG respectively) compared to untreated control. Significant increase in leaf area was also observed due to all the treatments of imidacloprid (429.27 to 431.63 and 403.61 to 406.24 cm2 in CP and GG respectively) followed by thiamethoxam (375.43 to 381.01 and 369.46 to 372.71 cm2 in CP and GG respectively) and acetamiprid (347.37 to 349.81 and 321.70 to 324.92 cm2 in CP and GG respectively) compared to the untreated control. No promoting effect was observed on number of root nodules and none of the three tested insecticides had any adverse effect on seed germination of these crops